Phytochemical Screening, Therapeutic Benefits, and Adverse Effects of Citrus aurantifolia - A Review - Chriscensia, Erika; Wibowo, Elizabeth Chrestella; Enriko, Gregorius; Wijaya, Owen Chrisfian; Sahamastuti, Agnes Anania Triavika (Indonesia International Institute for Life Sciences, 2020)
Key lime or Citrus aurantifolia has been well known for its functions, either as food or medicine. This fruit has a greenish-yellow color with a sour and bitter taste and distributed initially from East Asia. This review summarizes the phytochemical screening, therapeutic effects, and adverse effects of key lime. Most parts of the plant contain phytochemicals, such as phenols, flavonoids, steroids, terpenoids, and alkaloids, with other varying compounds like saponin, tannin, anthraquinone, glycosides, and carbohydrates that may be due to the country where the plant is grown, or the extraction methods. Some studies have been conducted to evaluate the therapeutic effects of key lime, including antibacterial, antioxidant, anticancer or antitumor, anti-cholesterol, anti-larvae, anti-mosquito, antidiabetic, anti-inflammatory, and anticholinesterase. Key lime also may cause some adverse effects, such as phytophotodermatitis. It may lead to toxicity manifested in conditions such as edema, inflammation, or necrosis in some organs in the body, an increase in lymphocytes & liver enzymes, and a decrease in hemoglobin.